Navigating the Dynamics of Speed in Football: Insights into Training, Genetics, and Developmental Strategies - Vuksanovikj, Vladimir; Kodjoman Kostadin; Aceski, Aleksandar; Spasovska, Katerina (Kondicija, 2024)
Fast movements are integral to speed as a human motor ability, and in the context of football, speed is considered a dominant ability. The manifestation of speed by elite players manifests a consistent upward trend over time. Although the existing literature lacks definitive data, the hereditary nature of this ability is frequently cited as a dominant factor in speed improvement. Crucial to enhancing speed is the implementation of training during the sensitive periods of children's development. Emphasis should be placed on developing the latent time of motor reactions, intricately tied to the central nervous system's maturation. Additionally, it is imperative to consider the energy component, with a focus on optimizing creatine phosphate stores (CP) when designing speed transformation training. During speed training sessions, it is advisable to limit the number of fast movements to a maximum of 30-40 repetitions, each lasting 5-10 seconds, with consideration for CP stores. Morning training sessions are recommended due to the heightened efficiency of the central nervous system, a crucial system responsible for delivering information that triggers muscle contractions. While sprinting (fast running) is a fundamental exercise from a methodological standpoint, a holistic approach should be adopted, incorporating various equipment such as ladders, and different methods including changes of direction. Genetic predictions of muscle fiber types in the human body are determined through the ACTN3 gene, specifically the mutation of the R577X allele. This mutation is regarded as a factor in determining the hereditary component of speed. However, the inclusion of genetic factors in the success of speed transformation is a complex matter. The primary focus for speed development should be in childhood. Young players should enhance this ability through various aspects of the game, extending beyond isolated training with quick movements. Such a holistic approach contributes not only to the overall development of young players but also fosters a passion for football, encouraging a lifelong engagement with the sport.
Keywords: football; speed; motor ability; heredity; speed training